(3TQM BOGH WGT cHQj RGOgs - (3eLghds
(3ChdgG (B:s
(3GdMeO ddg GdPj dG eGfY dYWGFg hdG eYGQV dbVGFg abO cfJ cJHJ YOI ef GdSWhQ eY bdI GdHVGYI hcKQI GdaJhQ aj GdefGXQI hGdBOGH hbO bUOJ GdGJj s
(3BNQgG (B:s
(3hJGSYgG Cfg dG jfHZj Gf dG jMSH GdefGXQ GdNUe MbjQG dGf GSJNMbGQ GdNUe QHeG jDOj Zdi UOhQ GdcdGe GdVYja Yf GdefGXQ ajchf SHHG dZdHI GdNUe GdVYja JeJs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdadSaI hGdefWbs